Sociologie et vecteurs de la popularité : l'mpact de la réception féminine sur la chanson québécoise des années 1940 - Savoie, Chantal (25 ans de sociologie française de la musique en France. Réflexivité, écoutes, goûts, 2012)
Keywords: 1900-1999; 1940-1949; amériques; discipline; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; sofia

Les préférences musicales des lectrices du Bulletin des agriculteurs, 1939-1955 - Savoie, Chantal (Communication. Information médias théories pratiques, 2006)
https://journals.openedition.org/communication/1496
Keywords: 1900-1999; 1930-1939; 1940-1949; 1950-1959; DIG; amériques; arts; culture populaire; discipline; musique; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; études littéraires

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis